Body perceptions, occupations, eating attitudes, and behaviors emerged during the pandemic: An exploratory cluster analysis of eaters profiles - Monthuy-Blanc, Johana; Corno, Giulia; Bouchard, Stéphane; St-Pierre, Marie-Josée; Bourbeau, Francisca; Mostefa-Kara, Leïla; Therrien, Émie; Rousseau, Michel (Frontiers in Psychology, 2022)
Introduction. COVID-19 pandemic negatively impacted people’s mental and physical health. Three areas have been significantly impacted, among others: eating-related behaviors, occupational balance and exposure to self-image due to videoconferencing. This study aims to explore and document eater profiles that were reported during the pandemic in the general Canadian population using a holistic perspective, including body perceptions, attitudes and eating behaviors (i.e., body image, behaviors, attitudes and motivations regarding food), and occupations (i.e., physical activity and cooking). Methods. This cross-sectional study was conducted from May 29th to September 1st, 2020. 273 Canada’s residents, French speaking of 18 years of age and older participated to an online survey on behaviors, attitudes and motivations regarding food and eating as well as body image and occupations during the COVID-19 pandemic. A hierarchical cluster analysis was used to determine the eater profiles. One-way ANOVA and chi-square test were conducted to differentiate occupational characteristics between eater profiles. Results. Three distinctive profiles were found during the COVID-19 pandemic and could be placed on a continuum: the Congruent-driven eater is at the functional pole of the continuum, whereas the Incongruent-driven eater is at the dysfunctional pole of the eater continuum. In the middle of the continuum, the Incongruent-perceptual eater is at a critical crossing point. Significant differences were reported between eater profiles. Discussion. The empirical results based on an eater continuum conceptualization highlight the importance of understanding how people perceive their body to assess and promote food well-being.